EMPOWERING RURAL WOMEN: DETERMINING FACTOR FOR SUSTAINABLE DEVELOPMENT IN TOURISM - Išpanović, Mina; Vujko, Aleksandra; Turčinović, Milena (The Business of Tourism, 2025)
Apstract: Empirical evidence suggests that the empowerment of rural women is an essential predictor of sustainable development in the tourism sector. As primary custodians of cultural capital and local traditions, their indispensable participation in community-based tourism initiatives significantly correlates with the improvement of economic sustainability, the preservation of cultural diversity, and the strengthening of social cohesion. This study investigates the causal relationship between the empowerment of rural women and tourism development, analyzes strategies for the amplification of their participation, and identifies inherent challenges. The central finding of the study implies that the empowerment of women is a key determinant of their inclination towards entrepreneurial activities within the domain of tourism.